Preparation and characterization of poly(maleic acid)-grafted cross-linked chitosan microspheres for Cd(II) adsorption. (15th September 2017) - Yu, Zhenzhen; Dang, Qifeng; Liu, Chengsheng; Cha, Dongsu; Zhang, Haifeng; Zhu, Wenjing; Zhang, Qianqian; Fan, Bing
Highlights: PMACCMs were prepared by grafting poly (maleic acid) to cross-linked chitosan microspheres (CCMs). PMACCMs possessed large numbers of carboxyl groups at C2–NH2, C6–OH, and C3–OH. The maximum adsorption capacity for Cd(II) of PMACCMs increased by 2.7 times as compared with that of CCMs. PMACCMs adsorption mechanism was investigated based on FTIR and zeta potential analyses. PMACCMs exhibited outstanding adsorption capability and reusability, and might be suitable candidate for wastewater purification. Abstract: A novel adsorbent, composed of poly(maleic acid)-grafted cross-linked chitosan microspheres (PMACCMs), was prepared via cross-linking with glutaraldehyde and modification by grafting maleic acid. FTIR, zeta potential, elemental analysis, 13 C NMR, DTG, laser particle size analysis, SEM, and BET methods were applied to characterize PMACCMs, exhibiting a successful fabrication, good thermostability, and well-defined surface microstructure beneficial to Cd(II) adsorption. The effects of pH, contact time, and initial concentration on Cd(II) adsorption were also investigated, and the maximum adsorption capacity was 39.2 mg g −1, indicating a great improvement as compared with that (14.5 mg g −1 ) of cross-linked chitosan microspheres. The experimental data were well fitted with pseudo-second-order kinetic and Langmuir isotherm models. Five-cycle reusability tests demonstrated PMACCMs could be repeatedly used with a small adsorption capacity loss (<15%). Additionally, the adsorption mechanism was proposed. All the results confirmed that PMACCMs, which presented outstanding adsorption capability and reusability, could be a good candidate for wastewater purification.